Ab initio study of the low-lying electronic states of YbCl molecule including spin-obit effects. (September 2018) - Chmaisani, Wael; Korek, Mahmoud
Highlights: Investigation of fourteen Λ−S and seven Ω low-lying states of the YbCl molecule. A ro-vibrational calculation with Einstein coefficients and dipole moments. Franck–Condon calculation and discussion for laser cooling experiments. Abstract: Ab initio quantum chemistry calculations for the low-lying electronic states of YbCl molecule, including the spin-orbit effects, have been performed via the CASSCF/MRCI (single and double excitations with Davidson correction) method. Adiabatic potential energy curves have been investigated for the low-lying electronic states in the 2s+1 Λ (+ /−) and Ω representations. Static dipole moment curves of the most investigated states are also computed. The spectroscopic constants and the percentage ionic character fionic of the lowest doublet and quartet bound states are calculated. The transition dipole moments, the spontaneous radiative lifetime and some emission coefficients are determined for the lowest electronic transitions. By using the canonical functions approach, the ro-vibrational parameters are also determined for different bound states. New theoretical data is studied in this work. The Franck–Condon factors (FCFs) for transitions involving the low vibrational levels of the (2)1/2, (1)3/2 and (3)1/2 states are highly diagonally distributed, unlike the other investigated electronic transitions. The off-diagonal FCFs of the transitions between the lowest-excited states and the ground state, indicate that direct laser cooling of the studied molecule is experimentally difficult. Graphical abstract: PECs for fourteen Λ–S and seven Ω states of YbCl are investigated at MRCI + Q level of theory. The general pattern of YbCl was assigned where the dipole moments, spectroscopic constants, ro-vibrational parameters, FCFs, and transition properties have been studied for these low-lying electronic states. Image, graphical abstract